Plan de negocios para la creación de una aplicación móvil que serviría de plataforma para la compra de pasajes de buses en la ruta interprovincial Quito-Guayaquil, Guayaquil-Quito - Lucas Farfán, Bernardo Josué (2016)
The services in this country require modernization as the process of purchasing bus tickets for travel within provinces can be an initial step for the technology to modernize the service. There is a business opportunity with the focus of covering routes from Quito-Guayaquil, Guayaquil-Quito, with a vision of expanding the business with more routes in Ecuador. The clients are the users of the bus system who have experienced the change in micro-terminals from the north to south of Quito in Quitumbe. The clients are required to go to the microterminal twice, once to purchase the ticket and the second to board the busses. There are also occasions when the clients travel to the bus terminal, make lines, just to find there are no tickets times of the year like the holidays. The idea consists of establishing a business that allows the purchase of interprovincial bus tickets through a mobile application platform, IOS or Android, in which the user downloads the free application and will be capable of purchasing a bus ticket through a agile, user friendly interface, fast, and with a guarantee of a safe payment process. The client will pay a fee for the use of the platform. The project undertaken has been an investigation through different parts of a business plan. With internal and external analysis, a survey, market investigation, orientation and philosophy of a organizational structure, financial costs and finally the establishment of the idea the business is feasible.